Parent–child relationship and parents' psychological well-being among Malaysian families amid pandemic: The role of stress and gender - Tan, Soon Aun; Pung, Pit Wan; Wu, Shin Ling *; Yap, Chin Choo *; Anusha, Raj Jayaraja; Chow, Brenda Gynn (Wiley, 2023)
The COVID-19 pandemic has taken most part of the world by surprise. The orders of nationwide movement control and social distancing by the Malaysian authority to curb the spread of the airborne virus have sent working-class families into a novel work-from-home condition. This study aimed to examine the association between positive experiences in parent–child relationships, parental stress and working parents' psychological well-being in Malaysia during the pandemic by considering the mediating role of parental stress and the moderating role of parental gender role. A total of 214 working-from-home parents (Mage = 46.39; SDage = 9.06; 51.9% working mothers; 76.6% Chinese) participated in a cross-sectional quantitative online survey. A significant positive relationship was found between parent–child relationships and parents' psychological well-being. Parental stress was negatively correlated with parent–child relationships and parents' psychological well-being. Meanwhile, parental stress significantly mediates the link between parent–child relationships and parents' psychological well-being. Besides, parental gender role was found to be a significant moderator where fathers experience better psychological well-being when they have more positive parent–child relationships. The findings further support the importance of positive interaction between parents and children and parental stress, which could affect parents' psychological well-being. This study may fill a knowledge gap by providing an overview of working parents' psychological well-being in their experience of working from home during the pandemic.